2015
DOI: 10.1007/s11120-015-0098-9
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of lanthanum(III) and cerium(III) ions between layers of manganese oxide on water oxidation

Abstract: Manganese oxide structure with lanthanum(III) or cerium(III) ions between the layers was synthesized by a simple method. The ratio of Mn to Ce or La in samples was 0.00, 0.04, 0.08, 0.16, 0.32, 0.5, 0.82, or 1.62. The compounds were characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction studies, and atomic absorption spectroscopy. The compounds show efficient catalytic activity of water oxidation in the presence of cerium(IV) ammonium nitrate with a turnover frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Based on additional X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) studies, it was suggested that potassium might be involved in forming distinct KCo 3 O 4 cubanes, although other studies have debated such a role for potassium . The influence of redox-inactive metals on water oxidation has been studied more extensively in manganese oxides that are structurally similar to the birnessite family of minerals. These manganese oxides form layers of edge-sharing MnO 6 octahedra, in which redox-inactive metals can intercalate . Studies on these synthetic mixed-manganese oxides revealed that, in the presence of redox-inactive metals, a marked increase in O 2 evolution was observed compared to plain manganese oxide. , The O 2 evolution activity followed the trend Ca 2+ > Sr 2+ ≫ Mg 2+ ∼ Na + , very similar to the activity profile of the OEC.…”
Section: Lewis Acid Effects On O2 Evolutionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on additional X-ray absorption near-edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) studies, it was suggested that potassium might be involved in forming distinct KCo 3 O 4 cubanes, although other studies have debated such a role for potassium . The influence of redox-inactive metals on water oxidation has been studied more extensively in manganese oxides that are structurally similar to the birnessite family of minerals. These manganese oxides form layers of edge-sharing MnO 6 octahedra, in which redox-inactive metals can intercalate . Studies on these synthetic mixed-manganese oxides revealed that, in the presence of redox-inactive metals, a marked increase in O 2 evolution was observed compared to plain manganese oxide. , The O 2 evolution activity followed the trend Ca 2+ > Sr 2+ ≫ Mg 2+ ∼ Na + , very similar to the activity profile of the OEC.…”
Section: Lewis Acid Effects On O2 Evolutionmentioning
confidence: 99%
“… 267 The influence of redox-inactive metals on water oxidation has been studied more extensively in manganese oxides that are structurally similar to the birnessite family of minerals. 36 40 These manganese oxides form layers of edge-sharing MnO 6 octahedra, in which redox-inactive metals can intercalate. 37 Studies on these synthetic mixed-manganese oxides revealed that, in the presence of redox-inactive metals, a marked increase in O 2 evolution was observed compared to plain manganese oxide.…”
Section: Lewis Acid Effects On O 2 Evolutionmentioning
confidence: 99%
See 2 more Smart Citations